2020
DOI: 10.1097/qad.0000000000002771
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA haplogroups and weight gain following switch to integrase strand transfer inhibitor-based antiretroviral therapy

Abstract: Background: Integrase strand transfer inhibitor (INSTI)-based antiretroviral therapy (ART) has been associated with excess weight gain in some adults, which may be influenced by genetic factors. We assessed mitochondrial DNA (mtDNA) haplogroups and weight gain following switch to INSTI-based ART. Methods: All AIDS Clinical Trials Group A5001 and A5322 participants with mtDNA genotyping who switched to INSTI were included. mtDNA haplogroups were derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Amongst AIDS Clinical Trials Group participants, persons with European mtDNA haplogroup clade UK and African haplogroup L3 had significantly greater weight gain after switching to INSTI-based ART, especially to regimens concomitantly using TAF [20 ▪ ], which could provide a window into observed race-based differences in weight gain with INSTIs and TAF.…”
Section: Pathogenesis Underlying Advent Of Antiretroviral Therapy-ass...mentioning
confidence: 99%
“…Amongst AIDS Clinical Trials Group participants, persons with European mtDNA haplogroup clade UK and African haplogroup L3 had significantly greater weight gain after switching to INSTI-based ART, especially to regimens concomitantly using TAF [20 ▪ ], which could provide a window into observed race-based differences in weight gain with INSTIs and TAF.…”
Section: Pathogenesis Underlying Advent Of Antiretroviral Therapy-ass...mentioning
confidence: 99%
“…32 Indeed, a recent study has shown differences in weight gain within White, Black, or Hispanic cohorts who switch to INSTIbased regimens may be associated with differences in genetic markers related to ancestry; however, the study sample included too few people of Hispanic ethnicity to draw firm conclusions. 33 Interpretation of our results is also complicated by the inclusion of both females (25%) and males (75%) in the Hispanic study population. As mentioned previously, several studies have reported differences between genders in ARV-related weight gain.…”
Section: Discussionmentioning
confidence: 84%
“…Some studies have shown an association between ARV-related weight gain and/or body mass index changes and certain populations such as women and Black and Hispanic populations. However, further study is warranted to understand both of what predictors, if any, exist for this phenomenon, as well as the cardiovascular and metabolic implications associated with weight gain [13,[125][126][127][128][129][130].…”
Section: Safety/adverse Effectsmentioning
confidence: 99%